Une campagne nationale : le versement des archives des haras nationaux - Pascal Even; Coraline Coutant-Daydé (In Situ, 2012)
At the end of 2005, when the General Public Policy Review engaged the restructuration of the French national stud-farms, the Direction des Archives de France gave attention to their archives, very often managed by their own administration. Then was launched a special campaign for the transfer of this historic archives throughout the country. When we take stock of this operation, we can assess the involvement of the departmental archives services and the exceptional richness of the collections, emphasized by expositions and publications.